Pretreatment with IPA ameliorates colitis in mice: Colon transcriptome and fecal 16S amplicon profiling - Fu, Yawei; Gao, Hu; Hou, Xiaohong; Chen, Yue; Xu, Kang (Frontiers in Immunology, 2022)
3-Indolepropionic acid (IPA) is a tryptophan metabolite that has anti-inflammatory properties. The present study try to investigated the phylactic effects of IPA on DSS-induced colitis mice. The results showed that IPA pretreatment ameliorated the DSS-induced decrease in growth performance, and intestinal damage and enhanced immunity in mice. RNA-seq analysis of mouse colon samples revealed that the differentially expressed genes (DEGs) were mainly enriched in immune-related pathways. 16S rRNA sequencing showed that IPA pretreatment ameliorated DSS-induced colonic microbiota dysbiosis. Moreover, the expression levels of gut immune genes were positively correlated with the relative abundance of several probiotics, such as Alloprevotella and Catenibacterium. In conclusion, IPA alleviates DSS-induced acute colitis in mice by regulating inflammatory cytokines, improving intestinal barrier function, balancing the colonic microbiota and modulating the expression of genes related to inflammation, which would also provide a theoretical basis for IPA as a strategy to improve intestinal health.